Portfolio d’options pour le renforcement de la résilience : application de principes systémiques de résilience à la gestion des risques d’inondation en Gironde - Touili Nabil (VertigO)
Coastal areas are currently facing a significant rise of frequency and severity of flood disasters combined with a high exposure of people and goods. While risk governance approaches call for changes to strengthen resilience coastal areas, flood risk management remains focused, in France, on land use planning control through inflexible and restrictive regulations. This paper aims at exploring empirically an alternative approach to flood risk management. By integrating resilience systemic principles, this paper offers an operational framework to adapt flood risk management to present and future risk on the coastal areas.